EFL Students’ Communication Strategies Used in Online and Face-to-Face Contexts: A Narrative Review - Damayanti, Lusi; Zur, Sarjaniah; Atikah, Dewi (IAIN KENDARI, 2024)
ABSTRACTThe English language is widely spoken worldwide and is the primary medium of cross-communication in international and intercultural contexts. This study is intended to analyze (1) the types of communication strategies (CSs) used by EFL students when they face the communication problem with the interlocutors and (2) the most frequent CSs used by EFL students when they interact in both face to face (F2F) and online contexts. This research applied a narrative review study with analysis content as a qualitative methodological approach. In total, there were 38 relevant articles reviewed, which consisted of 30 articles for F2F and 8 articles for online context. The current study used typology by and Nakatani, (2014) to analyze the CSs’ types. The results revealed that EFL students employ 34 various CSs; however, fillers strategy is the most frequent CSs used in the F2F environment. Meanwhile, the code-switching strategy is the most commonly used in an online environment. Thus, this research has implications for foreign language teaching in higher education for both lecturers and students. Lecturers may design activities and lessons that focus on practicing and developing students' proficiency in using various CSs.Keywords: Communication strategies; EFL students; face-to-face environment; online context